Remote teaching: experience and experiences of pedagogical residents in high school biology classes (Research, Society and Development, 2022)
To contain the speed of spread of Covid-19, the MEC pointed out a way, exceptionally authorized remote teaching, insofar as professionals used technological means of information and communication. Pedagogical Residency (RP) is one of the federal government programs, whose purpose of the initiative is to support higher education institutions in the implementation of innovative projects that stimulate the articulation between theory and practice in undergraduate courses. The final stages of graduation are faced with great barriers, but the scenario is even more difficult amid the pandemic. In this sense, this study aims to report the experience and experience of pedagogical residents in biology classes in high school, facing the return teaching. This is a study developed by academics/scholarship holders of the Pedagogical Residency Program (RP) of the biology subproject of the State University of Alagoas (UNEAL), in one of the partner schools, under the supervision of the preceptor of Biology at the Costa Rêgo State School, located in the city of Arapiraca-AL. In view of the reports obtained by the residents, satisfaction was perceived in working remotely in high school biology classes, as they claim how challenging and enriching the program was for their personal and professional trajectories. Thus, it is concluded that in the face of the current pandemic scenario, even with the difficulties exposed, this experience was of great value through the knowledge obtained in this program towards the experience of remote teaching, because through it, the academic will have direct contact with the future profession.